Prevalence and correlates of obstructive sleep apnoea among patients with and without HIV infection. Issue 2 (17th September 2014) - Kunisaki, KM; Akgün, KM; Fiellin, DA; Gibert, CL; Kim, JW; Rimland, D; Rodriguez‐Barradas, MC; Yaggi, HK; Crothers, K
<x xml:space="preserve">Abstract</x> Objectives In HIV‐uninfected populations, obstructive sleep apnoea (OSA) is commonly associated with cardiovascular disease, metabolic syndrome, and cognitive impairment. These comorbidities are common in HIV‐infected patients, but there are scarce data regarding OSA in HIV‐infected patients. Therefore, we examined the prevalence and correlates of OSA in a cohort of HIV‐infected and uninfected patients. Methods An observational cohort study was carried out. Electronic medical record and self‐report data were examined in patients enrolled in the Veterans Aging Cohort Study (VACS) between 2002 and 2008 and followed until 2010. The primary outcome was OSA diagnosis, determined using International Classification of Diseases, 9th edition (ICD‐9) codes, in HIV‐infected compared with uninfected individuals. We used regression analyses to determine the association between OSA diagnosis, symptoms and comorbidities in adjusted models. Results Of 3683 HIV‐infected and 3641 uninfected patients, 143 (3.9%) and 453 (12.4%) had a diagnosis of OSA (p < 0.0001), respectively. HIV‐infected patients were more likely to report symptoms associated with OSA such as tiredness and fatigue. Compared with uninfected patients with OSA, HIV‐infected patients with OSA were younger, had lower body mass indexes (BMIs), and were less likely to have hypertension. In models adjusting for these traditional OSA risk factors, HIV infection was associated with markedly reduced odds of OSA diagnosis (odds ratio 0.48; 95% confidence interval 0.39‐0.60). Conclusions HIV‐infected patients are less likely to receive a diagnosis of OSA. Future studies are needed to determine whether the lower prevalence of OSA diagnoses in HIV‐infected patients is attributable to decreased screening and detection or to a truly decreased likelihood of OSA in the setting of HIV infection.